Respuesta :
First solution: (x) - 2(y) = -8
Second solution: 4(x) + (y)
For the fraphic of the "respresentation" on the equation becomes: -2(y) + x = -8; (y) + 4(x) = 13
Now, let's do it this way: x - 2(-4[x] + 13) = -8
9(x) = 18
We found the the x-intercept (which is 2)
(y) = -4(x)
(y) = -4 × 2 + 14 = 5
x-intercept = 2; y-intercept = 5
Therefore,for your result we came upwith the answer of {2,5}
Good Luck :)
Second solution: 4(x) + (y)
For the fraphic of the "respresentation" on the equation becomes: -2(y) + x = -8; (y) + 4(x) = 13
Now, let's do it this way: x - 2(-4[x] + 13) = -8
9(x) = 18
We found the the x-intercept (which is 2)
(y) = -4(x)
(y) = -4 × 2 + 14 = 5
x-intercept = 2; y-intercept = 5
Therefore,for your result we came upwith the answer of {2,5}
Good Luck :)